2020
DOI: 10.1016/j.heliyon.2020.e04165
|View full text |Cite
|
Sign up to set email alerts
|

Tight expression regulation of senataxin, linked to motor neuron disease and ataxia, is required to avert cell-cycle block and nucleolus disassembly

Abstract: The Senataxin (SETX) protein exhibits strong sequence conservation with the helicase domain of the yeast protein Sen1p, and recessive SETX mutations cause a severe ataxia, known as Ataxia with Oculomotor Apraxia type 2, while dominant SETX mutations cause Amyotrophic Lateral Sclerosis type 4. SETX is a very low abundance protein, and its expression is tightly regulated, such that large increases in mRNA levels fail to significantly increase protein levels. Despite this, transient transfection in cell culture c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
(51 reference statements)
1
8
0
Order By: Relevance
“…Yet, despite tight SETX regulation, transient transfection can boost SETX levels on an individual cell basis. We found that by transient transfection of HEK293 cells, GFP-SETX was localized to the nucleoplasm, as expected (Bennett et al, 2020). But surprisingly, the nucleolus marker fibrillarin was diffused within the nucleus, coincident with SETX transfection.…”
Section: Setx Induces S-phase Arrestsupporting
confidence: 85%
See 1 more Smart Citation
“…Yet, despite tight SETX regulation, transient transfection can boost SETX levels on an individual cell basis. We found that by transient transfection of HEK293 cells, GFP-SETX was localized to the nucleoplasm, as expected (Bennett et al, 2020). But surprisingly, the nucleolus marker fibrillarin was diffused within the nucleus, coincident with SETX transfection.…”
Section: Setx Induces S-phase Arrestsupporting
confidence: 85%
“…Curiously, the SETX-induced fibrillarin redistribution appeared typical of prophase induction (Hernandez-Verdun, 2011), prompting us to test cell cycle progression with propidium iodide staining and flow cytometry. We found that GFP-SETX positive cells were S-phase arrested, without evidence of increased cell death (Bennett et al, 2020).…”
Section: Setx Induces S-phase Arrestmentioning
confidence: 68%
“…In another study, Bennet et al induced SETX over-expression that disrupted the cell cycle of HEK 293 cells and they concluded that neurons due to their long RNA transcripts (i.e. propensity for R-loops) may be particularly vulnerable if SETX expression is outside the optimal range [50].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Bennet et al induced SETX over-expression that disrupted the cell cycle of HEK 293 cells and they concluded that neurons due to their long RNA transcripts (i.e. propensity for R-loops) may be particularly vulnerable if SETX expression is outside the optimal range 52 .…”
Section: Discussionmentioning
confidence: 99%